Strategi Bertahan Dan Adaptasi Pelaku Usaha Pertashop Mini : Studi Kasus Di Kabupaten Bungku Morowali - Nur Sriani; Wa Ode Rayyani (CV. ITTC INDONESIA, 2025)
This study aims to analyze the survival strategies and forms of adaptation carried out by Pertashop Mini business actors in Bungku Regency, Morowali in facing internal and external challenges. Pertashop Mini businesses, as part of the micro energy distribution program by PT Pertamina, have an important role in expanding energy access in rural areas. However, business actors face various challenges, such as limited fuel supplies, high operational costs, competition with illegal retailers, and minimal technical support and training. Using a descriptive qualitative approach and data collection techniques in the form of semi-structured interviews, field observations, and documentation studies, this study found that common survival strategies applied include operational efficiency, strict stock management, and focus on loyal customers. Meanwhile, adaptation is carried out through the use of simple technology, service innovation, and strengthening social relations with the surrounding community. Local social capital, such as community trust and support from village officials, is a key factor in maintaining business continuity. This study concludes that the success of business actors in surviving and adapting is greatly influenced by the ability to manage social resources and respond to local market dynamics. Recommendations are given to business actors, local governments, and BUMDes to strengthen technical support, entrepreneurship training, and institutional collaboration for the sustainability of businesses in the micro energy distribution sector.